A Perspective from New York of COVID 19: Effect and impact on cardiac surgery. Issue 5 (16th September 2020) - Farrington, Woodrow J.; Mack, Charles A.; Karas, Maria G.; Ivascu, Natalia S.; Robinson, N. Bryce; Iannacone, Erin; Lau, Christopher; Mick, Stephanie L.; Girardi, Leonard N.
Abstract: Background and Aim: First reported in December of 2019, the COVID‐19 pandemic caused by SARS‐CoV‐2 has had a profound impact on the implementation of care. Here, we describe our institutional experience with a rapid influx of patients at the epicenter of the pandemic. Methods: We retrospectively review our experience with the departments of cardiology, cardiothoracic surgery, anesthesia, and critical care medicine and summarize protocols developed in the midst of the pandemic. Results: The rapid influx of patients requiring an intensive level of care required a complete restructuring of units, including the establishment of a new COVID‐19 negative unit for the care of patients requiring urgent or emergent non‐COVID‐19 related care including open‐heart surgery. This unique unit allowed for the delivery of safe and effective care in the epicenter of the pandemic. Conclusions: Here, we demonstrate the response of a large tertiary academic medical center to the COVID‐19 pandemic. Specifically, we demonstrate how rapid structural changes can allow for the continued delivery of cardiac surgical care with similar outcomes as those reported before the pandemic.